Odpowiedzi

2010-03-24T09:29:19+01:00
A) 4(x+3)=5x - 19
4x + 12 = 5x - 19
4x - 5x = -19-12
-x = -31 /: (-1)
x = 31

b)2(2m-3)+2m=5(3-m)+1
4m - 6 + 2m = 15 - 5m + 1
4m + 2m + 5m = 16 + 6
11m = 21 / : 11
m = 1, 10/11

c) 1,2-1,9x=0,5(x+3)-0,3(x+5) /*10
12 - 19x = 5(x+3) - 3(x+5)
12 - 19x = 5x + 15 - 3x -15
-19x - 5x + 3x = 15-15 - 12
-21x = - 12 / : (-21)
x = 12/21
2010-03-24T09:29:41+01:00
A)
4(x+3)=5x-19
4x+12=5x-19
4x-5x=-19-12
-x=-27 /*(-1)
x=27
b)
2(2m-3)+2m=5(3-m)+1
4m-6+2m=15-5m+1
6m+5m=16+6
11m=22 /:11
m=2
c)
1,2-1,9x=0,5(x+3)-0,3(x+5)
1,2 - 1,9x=0,5x+1,5-0,3x-1,5
-1,9x-0,2x=-1,2
-2,1x=-1,2 /:(-2,1)
x=12/21
x=4/7